ANALISIS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATA PELAJARAN SOSIOLOGI KELAS XI FASE F2 SMAN 1 X KOTO KABUPATEN TANAH DATAR - Wulandari, Putri; Akbar, Waza Karia; Erningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The research results showed that the application of the Jigsaw cooperative learning model was successful in increasing student participation, self-confidence and responsibility. This model is effective in helping students work in teams, improve their study skills, and understand the material more deeply. However, some challenges were also found, such as low motivation and responsibility among some students, and difficulties in managing large class sizes. Overall, the Jigsaw learning model is proven to create a more enjoyable and effective learning environment.